2020
DOI: 10.3389/fonc.2020.563700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Lymph Node Status on the Survival of Non-Small Cell Lung Cancer Patients With Brain Metastases: Applications of a Novel Grade Prognostic Assessment Score Model Involving N Stage

Abstract: Background: Grade prognostic assessment (GPA) is widely used to evaluate the prognosis of non-small cell lung cancer (NSCLC) patients with brain metastases (BMs). This study aimed to investigate whether lymph node status (LNS) could be included as one of the GPA variables for NSCLC with BMs. Methods: Overall, 586 patients with NSCLC and BMs were retrospectively analyzed. Overall survival stratified by LNS was analyzed using the Kaplan-Meier method. Multivariate analysis was also performed to identify independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This study showed that patients in group I who received aggressive treatment (primary tumor surgical resection and metastatic disease surgery and/or combined chemoradiotherapy) achieved long-term survival. This is consistent with many retrospective studies on stage IV lung cancer with oligometastasis (21)(22)(23)(24)(25). Although there was no statistically significant difference in OS between group I and group II in the multivariate analysis, there was a significant clinical difference (44 vs. 28 months; 39.6% vs. 21.3%).…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that patients in group I who received aggressive treatment (primary tumor surgical resection and metastatic disease surgery and/or combined chemoradiotherapy) achieved long-term survival. This is consistent with many retrospective studies on stage IV lung cancer with oligometastasis (21)(22)(23)(24)(25). Although there was no statistically significant difference in OS between group I and group II in the multivariate analysis, there was a significant clinical difference (44 vs. 28 months; 39.6% vs. 21.3%).…”
Section: Discussionsupporting
confidence: 91%
“…It has been recognized that the prognosis of cancer patients with brain metastases is affected by the status and the number of synchronous extracranial metastases(ECM), 28,29 and even the status of lymph node metastases 30 . However, which group of patients might develop brain oligometastases remained a problem.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that the prognosis of cancer patients with brain metastases is affected by the status and the number of synchronous extracranial metastases(ECM), 28 , 29 and even the status of lymph node metastases. 30 However, which group of patients might develop brain oligometastases remained a problem. In order to explore the distinct features of early‐stage lung adenocarcinoma patients who developed brain oligometastases, we compared brain‐only relapse (oligometastases) group with brain‐with relapse (synchronous ECM) group.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the integrative framework can be a useful clinical tool for personalized medicine. For instance, data from lymphatic bioimaging and patient information can be fed into artificial intelligence system and risk-scoring classification computational models to predict high-risk groups of cancer recurrence of LN metastasis [ [314] , [315] , [316] ]. By developing biochips with patient-derived biological materials, combinatorial drugs can be identified to treat cancer metastasis involving LNs.…”
Section: Discussionmentioning
confidence: 99%